Aplikasi Berbasis Web untuk Sistem Informasi Manajemen Aset: Modul Inventarisasi dan Penghapusan Aset (Studi Kasus: Yayasan Pendidikan Telkom, Kota Bandung) - Risma Nur Istiqomah; Tora Fahrudin; Raswyshnoe Boing Katjoprayudi (Universitas Telkom, 2024)
Yayasan Pendidikan Telkom is one of the Education Foundations in Indonesia which carries the concept of One PipeEducation System (OPES) and is spread throughout Indonesia. Companies have many assets to support their activitiesand these assets need to be managed in a structured and systematic manner. The condition of existing assets in thecompany needs to be periodically checked through an inventory to avoid assets that may be damaged but are not recordedwhich should be written off. In addition, asset write-offs at Yayasan Pendidikan Telkom are still handled manually whichresults in difficulties in managing them because the stages of write-off are quite complex. This research produces a solution,namely the development of a new application with its functionality, including asset inventory and deletion. The method usedin building this application uses the design of Use Case Diagrams, Entity Relationship Diagrams (ERD), Class Diagrams,Sequence Diagrams, Activity Diagrams, My Structured Query Language (MySQL) database, Hypertext Preprocessor (PHP)programming language, using the System Development Life Cycle (SDLC) method, namely prototyping and testing iscarried out using the Black Box Testing method, and based on application testing that has been done, the application canbe implemented